In situ fortification of vitamin B12 in wheat flour and wheat bran by fermentation with Propionibacterium freudenreichii. (May 2018) - Xie, Chong; Coda, Rossana; Chamlagain, Bhawani; Edelmann, Minnamari; Deptula, Paulina; Varmanen, Pekka; Piironen, Vieno; Katina, Kati
Abstract: Vitamin B12 is a micronutrient naturally existing in animal products. A growing interest and need to replace animal protein with plant protein sources have resulted in increased attention to developing vitamin B12-fortified plant-based food. Natural fortification by Propionibacterium freudenreichii is a promising alternative to chemical fortification, as P. freudenreichii can synthesize active vitamin B12. In this work, we studied vitamin B12 production in non-sterile matrices prepared from three raw materials of wheat: durum flour, wholewheat flour and wheat bran. Viable cell counts, pH, total titratable acidity and concentration of acids were determined. After seven days of fermentation, vitamin B12 levels reached 33 ± 4, 87 ± 10 and 155 ± 17 ng/g dry weight in durum flour, wholewheat flour, and wheat bran, respectively. While durum flour supported the growth of P. freudenreichii to higher cell densities and more efficient propionic acid production compared with the other two matrices, wholewheat flour and wheat bran were found to be the most promising of the three matrices for in situ production of vitamin B12. Highlights: Non-sterile wheat matrices maybe used for in situ production of vitamin B12. P. freudenreichii produced physiologically relevant amounts of vitamin B12. Wheat bran allowed higher production of vitamin B12 than other flours. Bran layer possibly contains precursors for vitamin B12 biosynthesis.